The Fate of 1,8-cineole as a Chemical Penetrant: A Review - Dao, Ligema; Dong, Yu; Song, Lin; Sa, Chula (Current Drug Delivery, 2024)
The stratum corneum continues to pose the biggest obstacle to transdermal drug delivery. Chemical penetrant, the first generation of transdermal drug delivery system, offers a lot of potential. In order to fully examine the permeation mechanism of 1,8-cineole, a natural monoterpene, this review summarizes the effects of permeation-enhancing medications on drugs that are lipophilic and hydrophilic as well as the toxicity of this substance on the skin and other tissues. For lower lipophilic drugs, 1,8-cineole appears to have a stronger osmotic-enhancing impact. An efficient and secure tactic would be to combine enhancers and dose forms. 1,8-cineole is anticipated to be further developed in the transdermal drug delivery system and even become a candidate drug for brain transport due to its permeability and low toxicity.
Keywords: 1